PENGARUH PEMBERIAN INFORMASI COVID-19 TERHADAP TINGKAT KECEMASAN PENULARAN COVID-19 PADA KELUARGA LANSIA - Agus Firman; Zahrah Maulidia Septimar; Ida Faridah (Nusantara Hasana Journal, 2023)
All nursing procedures provide information about the transmission of Covid-19, whether to elderly families or not, due to lack of knowledge about Covid-19 transmission. Covid-19 transmission. Objective to determine the effect of providing information on COVID-19 on the anxiety level of COVID-19 transmission in elderly families. This type of research is pre experimental, designed in the form of an experimental research design. The sample of this study was using total sampling, namely the entire population was sampled, namely as many as 85 families who had elderly people at home. The data was obtained by using the Zung Slef – Rating Axsiety Scale (Zung-S/RAS) questionnaire which provided information on the transmission of Covid-19. Univariate analysis using SPSS. Description of 85 respondents by age group 11-19 and 20-60 years, each of which is 8 (9%), and 77 people (90%), Most of them are male, namely 50 people ( 58%). The average score of anxiety on the effect of providing information on Covid-19 transmission is 57.8471 and most of the categories of mild anxiety are 55 (64%). There is an effect of providing information on Covid-19 transmission on the anxiety level of Covid-19 transmission in elderly families. There is an effect of providing information on the anxiety level of Covid-19 transmission in elderly families.